Determining the level of scientific literacy of high school and university students with the TOSLS test - Hejnová, Eva (Scientia in educatione, 2024)
The purpose of this study was to test the methodology for determining the level of scientific literacy of high school and university students using the Test of Scientific Literacy (TOSLS). 195 third- and fourth-year students from six high schools and 130 students from three Czech universities participated in the study. Descriptive and inductive statistical methods were used for data analysis. It was found that both high school and university students showed good results in skills aimed at evaluating the uses and misuses of scientific information, reading and interpreting graphical representations of the data, and solving problems using quantitative skills, including basic statistics. In contrast, they have difficulty with skills related to identifying strengths and weaknesses in research and understanding and interpreting basic statistics. In determining the levels of the sub-skills that define scientific literacy in the TOSLS, statistical analysis showed that test scores for all sub-skills depend on the group of students tested. The relatively low reliability found in the present study and in other international studies indicates the presence of several tasks that do not distinguish well between lower and higher scorers on the test.